VD_FINDINFO Arrêt / 2015 / 735 vom 28. September 2015 - VD Tribunal cantonal (2015)
ALLOCATION D'INITIATION AU TRAVAIL, RÉSILIATION, JUSTE MOTIF, RÉVOCATIONEN GÉNÉRAL | 337 CO, 65 LACI, 66 LACI, 90 OACI